SEROLOGICAL EVIDENCE OF LEPTOSPIRA SPP. IN THE LAMI TUCO-TUCO RODENTS (CTENOMYS LAMI) - Oliveira, Simone Tostes; Stein, Gisele Guiomara; Santos, Andrea Pires; Biondo, Alexander Welker; Messick, Joanne Belle; Gonzalez, Felix Hilario Diaz (Archives of Veterinary Science, 2014)
Although rodents are reportedly the major reservoirs of Leptospira spp. in the wildlife of Brazil, the role of the widely distributed native tuco-tuco rodent (Ctenomys lami) has yet to be determined. Accordingly, a total of 40 serum and eight urine samples from wild C. lami were collected from June to September 2008 in the city of Porto Alegre, Southern Brazil. The serum samples were screened using the Microscopic Agglutination Test against 13 Leptospira spp. pathogenic serovars. A polymerase chain reaction (PCR) was performed to detect the presence of leptospiral DNA in the urine samples. Five (12.5%) of the serum samples had >100 antibody titer levels against one or more of the serovars. None of the urine samples yielded a positive PCR amplification; however, all of the source animals were also negative. In conclusion, although C. lami may be exposed to Leptospira spp., infection may be occasional because no detectable leptospiruria was found.